IMPLEMENTASI BIMBINGAN KONSELING KLASIKAL MENGGUNAKAN TEKNIK SMALL GROUP DISCUSSION UNTUK MENINGKATKAN SELF CONTROL SISWA DI MA IRSYADUN NASI’IN KASIYAN - maulana, Puji; Putri, Zilmi Armanda (Journal of Education Counseling, 2024)
Adolescence is a period when a person experiences a transition from childhood to adulthood, from psychological and social aspects. Therefore, there are still many teenagers who are still unstable and cannot control themselves in positive things. This research is motivated by problems that arise at MA Irsyadun Nasi'in Kasiyan, namely students are still less able to control themselves in positive things, especially in the aspect of learning concentration. and learning discipline. So this research is a form of BK teacher's efforts to overcome problems related to self-control that exist at MA Irsyadun Nasi'in, especially in class XI IPS. The focus of this research is How to Implement Classical Guidance Counseling Using Small Group Discussion Techniques to Increase Student Self Control? And the sub-focus of this research includes: How to plan classical guidance counseling using small group discussion techniques to increase student self-control? How is the implementation of classical counseling guidance using the small group discussion technique to increase student self-control?, and how is the evaluation of classical counseling guidance using the small group discussion technique to increase student self-control? This research uses a descriptive qualitative approach. The technique for selecting subjects or samples in this research uses a purposive sampling technique, namely selecting samples/subjects based on certain criteria. Data collection techniques are observation, interviews and documentation, while at the data validity testing stage this research uses source triangulation. In this research, a conclusion was found that the implementation of classical guidance using small group discussion techniques went through three stages, namely planning, implementation and evaluation. The first is the guidance planning process which is carried out by proposing a class schedule and making an RPL, the second is the implementation stage which begins with an introduction or greeting, then the core activity which begins with the guidance and counseling teacher delivering material according to the RPL after that enters the discussion process, and the last is a process evaluation and results evaluation activity. By implementing Classical Guidance Using Small Group Discussion Techniques, it can be concluded that Classical Guidance activities can increase students' self-control, which is proven by the increased attitude and knowledge scores.